ESR, U-series and paleomagnetic dating of Gigantopithecus fauna from Chuifeng Cave, Guangxi, southern China. Issue 1 (July 2014) - Shao, Qingfeng; Wang, Wei; Deng, Chenglong; Voinchet, Pierre; Lin, Min; Zazzo, Antoine; Douville, Eric; Dolo, Jean-Michel; Falguères, Christophe; Bahain, Jean-Jacques
Abstract: Several Gigantopithecus faunas associated with taxonomically undetermined hominoid fossils and/or stone artifacts are known from southern China. These faunas are particularly important for the study of the evolution of humans and other mammals in Asia. However, the geochronology of the Gigantopithecus faunas remains uncertain. In order to solve this problem, a program of geochronological studies of Gigantopithecus faunas in Guangxi Province was recently initiated. Chuifeng Cave is the first studied site, which yielded 92 Gigantopithecus blacki teeth associated with numerous other mammalian fossils. We carried out combined ESR/U-series dating of fossil teeth and sediment paleomagnetic studies. Our ESR results suggest that the lower layers at this cave can be dated to 1.92 ± 0.14 Ma and the upper layers can be dated to older than 1.38 ± 0.17 Ma. Correlation of the recognized magnetozones to the geomagnetic polarity timescale was achieved by combining magnetostratigraphic, biostratigraphic and ESR data. The combined chronologies establish an Olduvai subchron (1.945–1.778 Ma) for the lowermost Chuifeng Cave sediments. We also analyzed the enamel δ 13 C values of the Gigantopithecus faunas. Our results show that southern China was dominated by C3 plants during the early Pleistocene and that the Gigantopithecus faunas lived in a woodland-forest ecosystem.